NEW MAYFLY NYMPHS FROM THE JURASSIC OF NORTHERN AND NORTHEASTERN CHINA (INSECTA: EPHEMEROPTERA) - Zhang J.F. (My University, 2006)
Four new species of mayfly nymphs, Furvoneta relicta sp. nov., Clavineta eximia sp. nov. (originally Mesoneta antiqua), Mesobaetis latifilamentacea sp. nov., and Stackelbergisca cylindrata sp. nov. are described from the Jurassic of China. All these species may have inhabited lakes rather than flowing water. The geological age and stratigraphical correlation of the nymph-bearing strata are briefly reviewed. © Pleiades Publishing, Inc. 2006.
Keywords: CHINA; EPHEMEROPTERA; INSECTA; JURASSIC; NYMPHS; Mesozoic::Jurassic; Мезозой::Юрская